Pediatric femoral shaft fractures secondary to tombstone uprooting – Two case reports. (April 2021) - Ali, Malik; Padhye, Kedar; Gauthier, Luke
Abstract: Case: Two cases are reported of femoral shaft fractures involving tombstones. A four and six year old child had similar histories of uprooting of tombstones during play, toppling them and causing injury. Treatment included non-operative and operative approaches, with both patients yielding bony union at the three month follow up. Conclusion: We present the involvement of tombstones as a unique mechanism of injury for femoral shaft fractures in two pediatric cases. From our review of the literature, we believe this to be a first report. We hope to highlight the associated safety implications for the primary prevention of a similar traumatic injury.